Topical Polypeptide Gel in Diabetic Ulcers: Clinical Insights Into a New Adjunctive Treatment Modality - Stella Gracia Octarica; Suci Widhiati; Endra Yustin Ellistasari; Nugrohoaji Dharmawan; Indah Julianto (Journal of Social Research, 2025)
Diabetic ulcers are a common and challenging complication of diabetes, contributing to morbidity, infection, and a high risk of amputation. Innovative adjuncts, such as topical polypeptide gel, which contains amino acids to support tissue regeneration, are proposed to accelerate wound healing; however, supporting clinical data are limited. A quasi-experimental analysis was conducted in 11 patients. Each received a daily topical 7% polypeptide gel in addition to standard care. Ulcer area was measured at baseline (day 0) and after 14 days using digital documentation analysis using ImageJ. The primary outcome was the percentage reduction in ulcer size. Patients were analysed for associations between percentage of improvement with age, gender, diabetes type, and ulcer site. Eleven patients with diabetic ulcers completed the 14-day treatment protocol. The cohort comprised 54.5% females with a mean age of 54.1 ± 7.3 years and predominantly insulin-dependent diabetes (72.7%). Baseline ulcer area averaged 982.1 ± 1315.1 mm², reducing to 184.0 ± 297.7 mm² by day 14, representing an 86.2 ± 6.7% mean area reduction. All patients achieved ?76% healing, with 45.5% achieving ?90% area reduction and 9.1% achieving complete healing. The Wilcoxon signed-rank test demonstrated statistically significant ulcer area reduction (Z = -2.934, p = 0.003). No significant associations were found between healing percentage and patient demographics, diabetes type, ulcer location, or comorbidity burden (all p > 0.05). No treatment-related adverse events were reported during the study period. Topical polypeptide gel demonstrated rapid wound surface area reduction in the majority of the subjects over 14 days, independent of patient age, gender, diabetes type, or ulcer location. These findings suggest its promise as an adjunctive early-phase therapy for diabetic ulcers.